2013
DOI: 10.1016/j.jneuroling.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Early stage visual-orthographic processes predict long-term retention of word form and meaning: A visual encoding training study

Abstract: Adult learners of Chinese learned new characters through writing, visual chunking or reading-only. Following training, ERPs were recorded during character recognition tasks, first shortly after the training and then three months later. We hypothesized that the character training effects would be seen in ERP components associated with word recognition and episodic memory. Results confirmed a larger N170 for visual chunking training than other training and a larger P600 for learned characters than novel characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 40 publications
2
41
1
Order By: Relevance
“…Although a more specific explanation requires further research, the current study shows that handwriting (a) increases the quality of the orthographic form and (b) selectively strengthens the connection from orthography to meaning (but not from orthography to phonology) for the population of adult Chinese learners. These findings are supported by a recent fMRI study (Cao et al, 2013a), in which left temporal lobe areas associated with meaning processing, as well as visual-spatial and motor areas, were activated during character reading for characters that had been learned with writing. Together, the studies suggest that meaning-focused learners can use their knowledge of Chinese orthography to complete the orthography-semantics association link.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Although a more specific explanation requires further research, the current study shows that handwriting (a) increases the quality of the orthographic form and (b) selectively strengthens the connection from orthography to meaning (but not from orthography to phonology) for the population of adult Chinese learners. These findings are supported by a recent fMRI study (Cao et al, 2013a), in which left temporal lobe areas associated with meaning processing, as well as visual-spatial and motor areas, were activated during character reading for characters that had been learned with writing. Together, the studies suggest that meaning-focused learners can use their knowledge of Chinese orthography to complete the orthography-semantics association link.…”
Section: Discussionsupporting
confidence: 77%
“…The current study along with Guan et al (2011) andCao et al (2013a) extends the writing effects from native Chinese children , native Chinese adults (Flores d'Arcais, 1994;Parkinson et al, 2010), alphabetic readers (Longcamp et al, 2005(Longcamp et al, , 2008 to adult Chinese L2 learners, who must attend to the visual features of the character in association with meaning and pronunciation as the learn characters. Cao et al (2013a) found that the early stage visual processing supports the acquisition of a visual representation that can support meaning and pronunciation connections in long-term memory.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations